2020
DOI: 10.1177/0165551520913817
|View full text |Cite
|
Sign up to set email alerts
|

Which are the influential publications in the Web of Science subject categories over a long period of time? CRExplorer software used for big-data analyses in bibliometrics

Abstract: What are the landmark papers in scientific disciplines? On whose shoulders does research in these fields stand? Which papers are indispensable for scientific progress? These are typical questions which are not only of interest for researchers (who frequently know the answersor guess to know them), but also for the interested general public. Citation counts can be used to identify very useful papers, since they reflect the wisdom of the crowd; in this case, the scientists using the published results for their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Recently, Thor et al . (2019) studied the highly influential publications of all WoS subject categories, i.e., journal sets. The results can be found online at www.crexplorer.net (WoS Landmark Papers).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Thor et al . (2019) studied the highly influential publications of all WoS subject categories, i.e., journal sets. The results can be found online at www.crexplorer.net (WoS Landmark Papers).…”
Section: Discussionmentioning
confidence: 99%
“…If a research area is analyzed, it is necessary to ensure that the research area is well represented in the database retrieval, taking into account the accuracy of the data in the literature included within the research area covered by the database. Therefore, the WoS database was selected for this study because it is the most commonly used source for bibliometric studies (Bornmann and Mutz, 2015), especially in the application of RPYS (Thor et al , 2016; Rhaiem and Bornmann, 2018; Thor et al , 2021). Fu and Zhang (2017) and Grosseck et al (2019) showed that the Science Citation Index Expanded (SCI-E) and Social Sciences Citation Index (SSCI) databases cover high-quality multilingual databases with more scientific and authoritative publications than any other database.…”
Section: Methodsmentioning
confidence: 99%
“…Marx et al (2013) first proposed the RPYS method. Based on peak citations in the references in publications in a specific research field over a year, RPYS can be used to discover early achievements with relatively few citations that are particularly important in the field of research, revealing pioneering research methods and important literature, both before and during the embryonic stage of a research field (Thor et al, 2016(Thor et al, , 2021. The advantage of RPYS is that publications from other fields that are cited in an archive can also be tracked, which is particularly important for the study of the historical roots of interdisciplinary fields.…”
Section: Reference Publication Year Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…CitedReferencesExplorer (CRExplorer) is a bibliometric analysis tool specifically focussing on cited references of a user defined database. Rooted in reference publication year spectroscopy (RPYS), CRExplorer identifies the historical roots of a research discipline by providing a graphical representation of key publications against a timescale (Thor et al, 2021). CRExplorer has been successfully used across academic disciplines (cf.…”
Section: Scientometric Analysis Techniquementioning
confidence: 99%